Effects of vegetative mulches on growth of indigenous crops in the Kingdom of Tonga. (26th January 2018) - Manu, V.; Whitbread, A.; Blair, G.
Abstract: As in many areas of the developing world, intensification of agriculture in Tonga, and other Pacific Islands, has put increased pressure on the soil resource. Two experiments were conducted to evaluate the effect of mulch on the growth and yield of two important food and fibre crops. The first was conducted on sloping land to evaluate the effect of guinea grass ( Megathyrsus maximus ) mulch and hedgerows on taro [ Colocasia esculenta (L.) Schott] yield, and in controlling soil erosion. The second compared the response of paper mulberry [ Broussonetia papyrifera (L) Ventenot] to different management regimes of a grass fallow. Thick vegetative mulch increased taro corm yield by 81% and reduced soil loss by 50% compared to local farmer practice, and the soil loss from taro with mulch was comparable to the perennial cash hedgerow treatment. Mulch increased paper mulberry bark yield by 30% compared to the non‐mulch control. Comparative economic analysis showed that increased net profit in the mulched treatments compared to the non‐mulched control was T2660/ha for taro and T12 108/ha for paper mulberry. Considering that mulch is readily available to many farmers throughout the Pacific Islands and elsewhere in the tropics, it is recommended as a sustainable practice for crop production.